KAJIAN LITERATUR: PERANAN TEKNOLOGI INFORMASI KESEHATAN PADA PERAWATAN DIABETES MELLITUS [LITERATURE REVIEW: THE ROLE OF HEALTH INFORMATION TECHNOLOGY IN THE CARE OF DIABETES MELLITUS] - Pina Pudiyanti; Tuti Afriani (Universitas Pelita Harapan, 2020)
People with diabetes mellitus must take responsibility for their own care to improve their quality of life. People with diabetes mellitus often need a set of services and support ranging from glucose monitoring, insulin and other treatment management, psychotherapy and social support, physical activity, nutritional counseling and others. Diabetes mellitus patients can play a more active role in treating their diabetes with health information technology. This literature review uses the PRISMA statement as a guide to search for research articles from two databases, Ebsco and Scopus. The results of the analysis of nine selected research articles indicate that information technology provides patient education and support for patients with diabetes mellitus. Information technology has been used to improve the quality of care for patients with diabetes mellitus, enable health workers to more effectively manage patients and to help patients manage their own illnesses so that research and related publications are needed to improve the care of patients with diabetes mellitus at home.BAHASA INDONESIA ABSTRAK: Penderita diabetes mellitus harus bertanggung jawab atas perawatan mereka sendiri untuk meningkatkan kualitas hidupnya. Penderita diabetes mellitus seringkali membutuhkan seperangkat layanan dan dukungan mulai dari pemantauan glukosa, insulin dan manajemen pengobatan lainnya, psikoterapi dan dukungan sosial, aktivitas fisik, konseling gizi dan lain-lain. Pasien diabetes mellitus bisa memainkan peran lebih aktif dalam perawatan diabetesnya dengan teknologi informasi kesehatan. Kajian pustaka ini menggunakan PRISMA statement sebagai panduan pencarian artikel penelitian dari dua database yaitu Ebsco dan Scopus. Hasil analisis sembilan artikel penelitian terpilih menunjukkan bahwa teknologi informasi memberikan pasien pendidikan dan dukungan pada pasien diabetes mellitus. Teknologi informasi telah digunakan untuk meningkatkan kualitas asuhan pasien diabetes mellitus, memungkinkan tenaga kesehatan lebih efektif mengelola pasien dan untuk membantu pasien mengelola sendiri penyakitnya sehingga penelitian dan publikasi terkait diperlukan untuk meningkatkan perawatan pasien diabetes mellitus di rumah.